Analysis of Polyculture Farm Cultivation Business and the Level of Welfare of Farmers in Muara Sembilang Family, Samboja District Kutai Kartanegara Regency - Miftakhul Huda; Said Abdussyahid; Heru Susilo (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
This study analyzes the brackish water pond polyculture system's business feasibility and identifies fish farmers' welfare level. This study was carried out in Muara Sembilang village located in Kutai Kartanegara Regency. The twenty fish farmers were selected as respondents by using the purposive sampling method. Data were examined by applying business analysis and fish farmer term of trade (NTPi) methods. Results showed that the average income of the brackish water pond polyculture system's business IDR1.950.701.047 per year. Also, fish farmers' welfare level using NTPi value indicated a value of 2.60 for household income and a value of 2.47 for fisheries business income, implying fish farmers' welfare level was very well. Keywords: income, welfare, polyculture, fish farmer term of trade.